E-Governance and Service Delivery by Rwanda National Public Service Commission - Uwingeneye, Gertrude; Akims, Malgit (Journal of Public Policy and Administration, 2024)
Purpose: This study examined the effect of E-governance and service delivery by Rwanda National Public Service Commission. The specific objectives of this study included, determining the effect of E-administration on service delivery by Rwanda National Public Service Commission and determining the effect of E-participation on service delivery by Rwanda National Public Service Commission. The three theories that provided the basis of this research are the following: Stakeholders Theory, Technology Acceptance Model and Expectancy Disconfirmation Theory. Chose these ideas because of what they have to say about how services are provided in a tech-driven setting. In order to accomplish these goals, an analysis of relevant literature was conducted. Methodology: Data were gathered from 47 randomly selected workers of the Rwanda National Public Service Commission using a census sample approach. Data was gathered using a combination of questionnaires and document analysis. As part of the study, SPSS 25 was used. Findings: The Rwanda National Public Service Commission found a high level of correlation (R = 0.844) between the predictors of service delivery and administration, and participation. With an R-squared value of 0.712, these variables account for around 71.2% of the variance in service delivery. Their unstandardized coefficients emphasize the impact of each predictor on service delivery. With a coefficient E-administration also has a notable positive effect, with a coefficient of (β = 0.404, t = 4.646, and p-value = 0.000). Similarly, E-participation contributes positively, with a coefficient of (β = 0.505, t = 5.973, and p-value = 0.000). All coefficients are statistically significant, underscoring their crucial roles in enhancing service delivery, as indicated by their p-values being below the conventional threshold of 0.05. Unique Contribution to Theory, Practice and Policy: The study recommended that Rwanda National Public Service Commission should enhance the user interface and accessibility of online platforms, expand online services while integrating with other government systems, and improve cybersecurity protocols.